Faktor yang Mempengaruhi Cakupan K4 Pemeriksaan Ibu Hamil di Puskesmas Bontomarannu, Kecamatan Galesong Selatan, Kabupaten Takalar - Zulhaedah Zulhaedah; Kasmawati Kasmawati; Fitri H. Sudiamin (Pusat riset dan Inovasi Nasional, 2025)
Every pregnant woman is strongly recommended to undergo comprehensive and quality antenatal care (ANC) at least four times, consisting of at least once in the first trimester (before 14 weeks of gestation), at least once in the second trimester (14–28 weeks of gestation), and at least twice in the third trimester (between 28–36 weeks and after 36 weeks of gestation), including at least one visit accompanied by the husband or a family member. The first ANC visit is highly recommended to be conducted between 8 and 12 weeks of gestation. The objective of this study is to identify the factors that influence the K4 coverage of antenatal visits among pregnant women at Bontomarannu Public Health Center, Galesong Selatan Subdistrict, Takalar Regency. This research uses a cross-sectional study design. The sample consisted of 60 pregnant women who underwent K4 antenatal examinations at Bontomarannu Public Health Center, selected through random sampling. The results showed that knowledge significantly affected the K4 coverage of antenatal visits (p = 0.000), occupation also had a significant influence (p = 0.004), and distance was another significant factor (p = 0.005). It can be concluded that knowledge, occupation, and distance all influence the K4 coverage of antenatal visits at Bontomarannu Public Health Center, Galesong Selatan Subdistrict, Takalar Regency.